Literature Analysis and Future Research Framework in Improvement and Substitutes Strategies - Yaumil Fauzan Malik; Dyah Poespita Ernawati (Eksis: Jurnal Riset Ekonomi dan Bisnis, 2021)
Abstract The aim of this paper is to examine improvement strategy using 4 approaches categorized as “substitutes for strategy” in operations strategy and to propose a framework for future research. This paper used a descriptive approach to examine peer-reviewed articles that were selected for analysis purposes. The analysis revealed that the majority of previous studies always used the principle of continuous improvement in 3 operating concepts, namely TQM, Lean, and Six Sigma, and the use of the breakthrough improvement strategy in the concept of Business Process re-engineering. Therefore, this study proposes a future research framework that is related to operational management concepts but uses the opposite improvement strategy approach. This article provides a future research framework that can be used as a basis for other researchers in the future to examine TQM, Six Sigma, Lean, and BPR from different perspectives of the improvement strategy. Professionals who worked in the operations field can use the framework provided in this article to view the company's strategy from a different perspective to gain a competitive advantage for their organization. Improvement Strategy, Continuous Improvement, Breakthrough Improvement, Total Quality Management, Lean Operations, Six Sigma, Business Process Re-engineering.